A model of the intracellular response of an olfactory neuron in Caenorhabditis elegans to odor stimulation. - Mamoru Usuyama; Chisato Ushida; Ryuzo Shingai (PLoS ONE, 2012)
We developed a mathematical model of a hypothetical neuronal signal transduction pathway to better understand olfactory perception in Caenorhabditis elegans. This worm has only three pairs of olfactory receptor neurons. Intracellular Ca(2+) decreases in one pair of olfactory neurons in C. elegans, the AWC neurons, following application of an attractive odor and there is a transient increase in intracellular Ca(2+) following removal of odor. The magnitude of this increase is positively correlated with the duration of odor stimulation. Additionally, this Ca(2+) transient is induced by a cGMP second messenger system. We identified likely candidates for the signal transduction molecules functioning in this system based on available gene expression and physiological data from AWCs. Our model incorporated a G-protein-coupled odor receptor, a G-protein, a guanylate cyclase as the G-protein effector, and a single phosphodiesterase. Additionally, a cyclic-nucleotide-gated ion channel and a voltage-gated ion channel that mediated calcium influx were incorporated into the model. We posited that, upon odor stimulation, guanylate cyclase was suppressed by the G-protein and that, upon cessation of the stimulus, the G-protein-induced suppression ceased and cGMP synthesis was restored. A key element of our model was a Ca(2+)-dependent negative feedback loop that ensured that the calcium increases were transient. Two guanylate cyclase-activating proteins acted on the effector guanylate cyclase to negatively regulate cGMP signaling and the resulting calcium influx. Our model was able to closely replicate in silico three important features of the calcium dynamics of AWCs. Specifically, in our simulations, [Ca(2+)] increased rapidly and reached its peak within 10 s after the odor stimulus was removed, peak [Ca(2+)] increased with longer odor exposure, and [Ca(2+)] decreased during a second stimulus that closely followed an initial stimulus. However, application of random background signal ('noise') showed that certain components of the pathway were particularly sensitive to this noise.